ECOLOGICAL STATE OF THE VOLYN REGION ENVIRONMENT AND ITS IMPACT ON HUMAN HEALTH - Мисковець, Ірина; Мольчак, Ярослав (SWorldJournal, 2022)
Abstract. The article considers the issues of negative impact on the human health of the environment. It demonstrates how health of the population of the certain region depends on the ecological state of the environment. Environmental factors are analyse